Pembreidelan Pers di Indonesia dalam Perspektif Politik Media - Triwardani, Reny (Jurnal ILMU KOMUNIKASI, 2010)
Abstract: To observe the dinamics of the press in Indonesia is very interesting as the development of national press can not be apart of socio-politics situation in this country. Even it can be told that the Ã¢â‚¬Å“live or deadÃ¢â‚¬Â of national press depends on how the ruler treat it. Historical facts inform us that media censorship has become a snate for press development time by time. In this connection, media censorship has become primary weapon to limit the press freedom in media politics applied by the ruler. It because media has a very important role in contemporary political arts. Press freedom is now a thing that journalists struggle to be happen. At the other hand, the ruler needs press to legitimate its power. This articles aim to analyze how media censorship had chained the press freedom in view of media politics. In this case, the ruler applies the press policy toward the press institution to secure its position and power.